2022
DOI: 10.3390/w14050833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pre-Analytical and Analytical Methods for Detecting SARS-CoV-2 in Municipal Wastewater Samples in Northern Italy

Abstract: (1) Background: The surveillance of SARS-CoV-2 RNA in urban wastewaters allows one to monitor the presence of the virus in a population, including asymptomatic and symptomatic individuals, capturing the real circulation of this pathogen. The aim of this study was to evaluate the performance of different pre-analytical and analytical methods for identifying the presence of SARS-CoV-2 in untreated municipal wastewaters samples by conducting an inter-laboratory proficiency test. (2) Methods: three methods of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, wastewater analysis provides insights into infectious trends in the population regardless of the availability of clinical testing data [ 21 ]. Environmental monitoring of SARS-CoV-2 has been extensively described also in various Italian regions [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], confirming it as a powerful tool for tracking the spread of SARS-CoV-2 variants/subvariants in the population [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, wastewater analysis provides insights into infectious trends in the population regardless of the availability of clinical testing data [ 21 ]. Environmental monitoring of SARS-CoV-2 has been extensively described also in various Italian regions [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], confirming it as a powerful tool for tracking the spread of SARS-CoV-2 variants/subvariants in the population [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of the genetic material of SARS-CoV-2 by concentration using PEG 8000 (which is based on the precipitation analyzes) has shown a better yield when compared to other techniques, such as occulation or ultracentrifugation 30,43,44 . Therefore, a lower concentration of organic matter (or reaction inhibitors) in the treated samples, as well as the application of a concentration technique capable of increasing the e ciencies of viral recovery may explain the superior performance of the positivity rate of the treated samples that were concentrated by PEG 8000 compared to the others analyzed in this study.…”
Section: Successful Detection Of Sars-cov-2 In Wastewater Samplesmentioning
confidence: 99%
“…Our keyword analysis revealed that scientists are actively investigating the issues of the basic complexities of wastewater and viral dilutions by using several sample pre-treatment and virus concentration steps [51][52][53]. Inter-laboratory comparisons for identifying the best concentration principles were also published [54]. Upon an in-depth manual analysis, we noted that most of the studies utilized a smaller wastewater volume (<250 mL); however, quite a few studies reported that an increased wastewater sample volume can enhance the overall sensitivity of WBE and that the use of ultracentrifugation techniques for virus concentration is apparently the most common one [55,56].…”
Section: Bibliometric Tracking Of the Research Trends By Abstractmentioning
confidence: 99%